Peran Wali Kelas Mengatasi Perilaku Agresif Siswa di SMAN 8 Mandau Duri Riau - Annisa Risky; Dodi Pasila Putra; Deswalantri Deswalantri; Linda Yarni (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This research was conducted in accordance with the phenomena that occurred at SMA N 8 Mandau which showed cases of students behaving aggressively such as fighting teachers, fighting with friends, making fun of friends and damaging school infrastructure. The homeroom teacher is the person closest to the students and has the authority to handle cases like this, because at SMA N 8 Mandau there is a rule that for any problems or inappropriate behavior caused by students, the homeroom teacher is the first to have authority. to deal with them. The purpose of this research is to find out how the role of the homeroom teacher is in overcoming the aggressive behavior of students at SMA N 8 Mandau. The research method that the writer uses is descriptive qualitative research. The informants in this study were the homeroom teacher of class XI IPS 3 as a key informant and two students of class XI IPS 3 who behaved aggressively as supporting informants. Data collection was carried out by interviews and observation, as well as documentation. While the data analysis technique used is to examine all data, data reduction, and data presentation. The results of the study explained that the homeroom teacher of SMA N 8 Mandau overcame aggressive behavior in the first way that was carried out by the homeroom teacher, namely seeking information or seeking the truth whether students were actually carrying out aggressive behavior. information from subject teachers who teach in classes whose students behave aggressively, then the homeroom teacher will reduce points and enter the student's name in the case book, then the homeroom teacher will call students who behave aggressively to be given individual counseling services and finally the homeroom teacher will call parents students who behave aggressively to discuss and find solutions to student problems with parents.